2019
DOI: 10.1177/0165025419866914
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the relation between preschoolers’ anger and persistence

Abstract: Although the functionalist perspective on emotional development posits that emotions serve adaptive functions, empirical tests of the role of anger mostly focus on how anger contributes to dysfunction. Developmentally, as children gain agency and skill at emotion regulation between the ages of 36 months and 48 months, their modulation of anger may facilitate its functional role for behavior. We examined this possibility through study of how 120 children’s anger and sadness were related to persistence during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
1
6
0
1
Order By: Relevance
“…Our findings demonstrate that children's emotions and persistence do indeed change during the task as theorized (Bridges & Grolnick, 1995;Cole et al, 2019;Lazarus, 1991). None of the groups showed a steady increase in persistence, and in all but one group, children's persistence decreased over time (albeit to different degrees), which was consistent with a previous study that found the likelihood of children giving up the task increased with time (Ramsook et al, 2020). In addition, our findings also suggest that it might be difficult for young children to increase or maintain regulatory efforts to achieve a goal even for just 2 to 4 min and add empirical evidence to the conceptualization that self-regulation operates as a finite resource which could be depleted through repeated use (Baumeister & Vohs, 2018;Muraven & Baumeister, 2000).…”
Section: Heterogeneity Of Trajectories In Anger Sadness and Persistencesupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings demonstrate that children's emotions and persistence do indeed change during the task as theorized (Bridges & Grolnick, 1995;Cole et al, 2019;Lazarus, 1991). None of the groups showed a steady increase in persistence, and in all but one group, children's persistence decreased over time (albeit to different degrees), which was consistent with a previous study that found the likelihood of children giving up the task increased with time (Ramsook et al, 2020). In addition, our findings also suggest that it might be difficult for young children to increase or maintain regulatory efforts to achieve a goal even for just 2 to 4 min and add empirical evidence to the conceptualization that self-regulation operates as a finite resource which could be depleted through repeated use (Baumeister & Vohs, 2018;Muraven & Baumeister, 2000).…”
Section: Heterogeneity Of Trajectories In Anger Sadness and Persistencesupporting
confidence: 90%
“…There have been a small but increasing number of studies that have reported empirical evidence supporting the functions of anger and sadness (Dennis et al, 2009; He et al, 2012; Lench & Levine, 2008; Ramsook et al, 2020; Tan & Smith, 2018). For instance, He et al (2012) found that higher levels of anger were related to higher levels of persistence during a goal blocking task in a sample of preschoolers.…”
Section: Dynamic Changes and Heterogeneity In Emotions And Persistencementioning
confidence: 99%
See 2 more Smart Citations
“…Pedagogical theories that focus their study on global educational processes and lifelong education reveal the importance of student emotions and affect in these processes, in that they contribute to the improved academic and social education of students [ 7 ]. In other words, a better regulation and management of emotions and affect provoke integral improvements to personality development at an individual level, and to society overall [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%